Islamic Sharecropping and Farmer Welfare: An Analysis of the Muzara‘ah System in West Lombok, Indonesia - Sindi Apriani; Habibul Umam Taqiuddin; Muhammad Yakub (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study investigates the implementation of the muzara‘ah profit-sharing system and its impact on farmer welfare in West Lombok, Indonesia, through the lens of Islamic economics. Using a qualitative descriptive approach, the research examines how Islamic sharecropping arrangements between landowners and tenant farmers influence income distribution, productivity, and social cohesion within rural communities. Data were collected through in-depth interviews, field observation, and documentation involving both landowners and sharecroppers in Bagik Polak Village, Labuapi District. The findings reveal that the muzara‘ah contract, conducted orally based on mutual trust and kinship, reflects key Islamic ethical principles such as amanah (trust), ‘adl (justice), and ta‘awun (mutual cooperation). The typical profit-sharing ratios—½:½ for rice and ⅓:⅔ for horticultural crops—provide equitable returns that enhance household income and strengthen community solidarity. Despite the absence of written agreements, the practice remains sharia-compliant, as it fulfills the essential requirements of muzara‘ah. However, sustainability challenges persist, including limited access to capital, the absence of formal documentation, and vulnerability to crop failure. The study concludes that the muzara‘ah system not only functions as an agricultural financing mechanism but also embodies a moral economy model that promotes fairness, productivity, and welfare within Islamic rural society.